beloun-01-01-001-a

$ \newcommand\tg{\operatorname{tg}} \newcommand\cotg{\operatorname{cotg}} \newcommand{\uhel}{{<}\kern-0.5em)\,} \newcommand\abs[1]{\left| #1 \right|} \newcommand\zav[1]{\left( #1 \right)} \newcommand\zavhra[1]{\left[ #1 \right]} \newcommand\zavslo[1]{\left\{ #1 \right\}} \newcommand\zavlom[1]{\left< #1 \, \right>} \newcommand{\podtrzeni}[1]{\underline{ #1 }} \newcommand{\vysledek}[1]{\underline{\underline{#1}}} \newcommand{\priume}[4]{ \Bigg\uparrow \underline{ \begin{array}{rp{2.3cm}r} #1 & \dots\dots\dots\dots\dots & #2 \\ #3 & \dots\dots\dots\dots\dots & #4 \end{array}} \Bigg\uparrow} \newcommand{\nepriume}[4]{ \Bigg\downarrow \underline{ \begin{array}{rp{2.3cm}r} #1 & \dots\dots\dots\dots\dots & #2 \\ #3 & \dots\dots\dots\dots\dots & #4 \end{array}} \Bigg\uparrow} \newcommand{\nepriumevpravo}[4]{ \Bigg\uparrow \underline{ \begin{array}{rp{2.3cm}r} #1 & \dots\dots\dots\dots\dots & #2 \\ #3 & \dots\dots\dots\dots\dots & #4 \end{array}} \Bigg\downarrow} $ $ \textbf{Běloun 1.1 a) / s. 7} $

$ \textbf{Vypočítejte} $
$$ 23-[2,6+(6-3^2)-4,52] $$
$ \textbf{Řešení} $ \begin{align*} &23-[2,6+(6-3^2)-4,52]=\\ =\ &23-[2,6+(6-9)-4,52]=\\ =\ &23-[2,6+(-3)-4,52]=\\ =\ &23-[-0,4-4,52]=\\ =\ &23-(-4,92)=\\ =\ &23+4,92=\\ =\ &\vysledek{27,92} \end{align*} $ \textbf{Výsledek} $ $$ \vysledek{27,92} $$
$ \textbf{Konec příkladu} $